Presidential Ideology and Immigrant Detention - Kim, Catherine Y. (2020)
In our nation’s immigration system, a noncitizen charged with deportability may be detained pending the outcome of removal proceedings. These individuals are housed in remote facilities closely resembling prisons, with severe restrictions on access to counsel and contact with family members. Due to severe backlogs in the adjudication of removal proceedings, such detention may last months or even years. Many of the noncitizens initially detained by enforcement officials have the opportunity to request a bond hearing before an administrative adjudicator called an immigration judge (“IJ”). Although these IJs preside over relatively formal, on-the-record hearings and are understood to exercise “independent judgment,” concerns have been raised that they are subject to control by political superiors in the executive branch. This Article analyzes approximately 780,000 custody decisions by IJs from January 2001 through September 2019 to explore the question of political influence over these adjudicators. Its bivariate analyses based on cross-tabulations, without additional controls, show that noncitizens have fared worse in bond proceedings during the Trump administration than they did during the prior two presidential administrations. Importantly, these differences were not limited to decisions rendered by Trump-appointed IJs. Rather, all IJs—regardless of the president whose Attorney General appointed them—have been more likely to deny bond or impose a higher bond amount during the Donald Trump Era than during the Barack Obama or George W. Bush (“Bush II”) Eras. Although this analysis does not control for the myriad of demographic, political, economic, geographic, and institutional factors that could impact decision-making, these findings call into question the political independence of IJs making decisions on noncitizen bonds